CircAHNAK upregulates EIF2B5 expression to inhibit the progression of ovarian cancer by modulating the JAK2/STAT3 signaling pathway. (17th June 2022) - He, Si-Li; Zhao, Xingping; Yi, Shui-Jing
Abstract: Recent studies highlighted non-coding RNAs as potential therapeutic targets in ovarian cancer. We aimed to investigate the roles of circAHNAK in ovarian cancer pathogenesis. Here, RNA immunoprecipitation, dual-luciferase reporter assay and RNA fluorescence in situ hybridization were adopted to determine circAHNAK, miR-28 or EIF2B5 interaction. CCK-8 assay was used to detect cell proliferation. Wound healing and Transwell assays were employed to assess cell migration and invasion, respectively. Flow cytometry was performed to measure cell apoptosis. The roles of circAHNAK on tumor growth in vivo were evaluated using subcutaneous xenograft model. The expression levels of circAHNAK, miR-28, EIF2B5, markers of EMT and JAK2/STAT3 pathway were measured by qRT-PCR, western blotting or immunohistochemistry staining. We reported that circAHNAK was decreased in ovarian cancer tissues. Forced expression of circAHNAK promoted apoptosis and inhibited cell proliferation, migration, invasion, EMT and JAK2/STAT3 signaling pathway. Mechanistically, circAHNAK acted as a miR-28 sponge. CircAHNAK deficiency resulted in the amassing of miR-28, which was elevated in ovarian cancer and promoted cancer cell malignancy. MiR-28 in turn inhibited EIF2B5 expression. Silence of EIF2B5 abolished the anticancer effects of miR-28 inhibitor. CircAHNAK overexpression retarded tumor growth in vivo, along with the decreased miR-28 and increased EIF2B, as well as EMT inhibition. In conclusion, circAHNAK targets miR-28 to upregulate EIF2B5 expression, thus inhibits progression of ovarian cancer by suppressing JAK2/STAT3 signaling pathway. Abstract : CircAHNAK sponged miR-28 to disinhibit EIF2B5, leading to the suppression of the JAK2/STAT3 signaling pathway and hence inhibiting the EMT and progression of ovarian cancer. Graphical Abstract: